Health-related fitness knowledge, physical activity attitude and physical activity in secondary school students: A mediation analysis - BOZDOĞAN, TUBA (My University, 2024)
Study aim: The aim of this study was to examine the mediating role of secondary school students’ physical activity attitudes between health-related fitness knowledge (HRFK) and physical activity (PA). Materials and methods: The research employed a quantitative research method, using the relational survey model. The participants of the study consisted of a total of 603 (female = 295, male = 308) secondary school students from six different secondary schools in Isparta and Burdur provinces in the fall semester of the 2023–2024 academic year. The data of the study were collected with a personal information form, the Turkish HRFK Test, the Physical Activity Attitude Scale for Secondary School Students and the Physical Activity Questionnaire for Older Children (PAQ-C). The analysis of the data was made using the Process Macro v3.3 plug-in with model 4 and 5000 resampling methods with a 95% confidence interval. Results: It was found that students’ HRFK had significant positive effect on their physical activity attitudes and physical activities. It was observed that physical activity attitudes also positively affected physical activity. Additionally, physical activity attitudes were found to have a mediating role between HRFK and physical activity. Conclusions: To conclude, it was found that secondary school students’ HRKF affected their participation in physical activity. However, our research showed that the effect of HRFK on physical activity of secondary school students may occur indirectly through physical activity attitudes. It can be concluded that the HRFK level of secondary school students is important for participation in physical activity.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; ORTOPEDİ; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; ORTHOPEDICS; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Ortopedi ve Spor Hekimliği; Physical Therapy, Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Attitude; Health; Knowledge; Physical activity